2022
DOI: 10.1007/s13132-022-01046-2
|View full text |Cite
|
Sign up to set email alerts
|

Successors’ Future Training in Family Farms: The Impact of Intrinsic and Extrinsic Factors

Abstract: This study examines the effects of different intrinsic and extrinsic-to-potential successors’ factors on the willingness of potential successors of family farms to continue training in the future. Building on socioemotional wealth (SEW) theory and a knowledge-based view, we consider the potential successors’ (yet students in agricultural schools) perspectives, and conceptually and empirically examine whether they believe intrinsic factors, namely, their own personal interest and willingness to create a new bus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 94 publications
0
2
0
Order By: Relevance
“…But their greatest hope, according to the scholarship, lies in their promise to revitalize smallscale farming. By providing a consistent local or regional market for farm products, food hubs have the potential to strengthen farmers' access to produce markets beyond the interventions of CSAs and farmers markets (Phillips & Wharton, 2016). By taking on the role of managing post-harvest sales and marketing activities, food hubs can perform a vital service that improves farmers' knowledge about market demand, and thus decreases the risk in knowing what to plant, at what time, and at what scale while also providing a reliable and consistent source of local and regional food to consumers (Hermiatin et al, 2022).…”
Section: Food Hubsmentioning
confidence: 99%
“…But their greatest hope, according to the scholarship, lies in their promise to revitalize smallscale farming. By providing a consistent local or regional market for farm products, food hubs have the potential to strengthen farmers' access to produce markets beyond the interventions of CSAs and farmers markets (Phillips & Wharton, 2016). By taking on the role of managing post-harvest sales and marketing activities, food hubs can perform a vital service that improves farmers' knowledge about market demand, and thus decreases the risk in knowing what to plant, at what time, and at what scale while also providing a reliable and consistent source of local and regional food to consumers (Hermiatin et al, 2022).…”
Section: Food Hubsmentioning
confidence: 99%
“…The traditional thought of small farmers is inevitably impacted by industrial culture. The relevant empirical research also shows that farmers' professional confidence and love for agriculture can well reflect farmers' professional willingness [54][55][56][57][58]. For those who think that farming is difficult, growing grain is a low-level industry, and it is not very comfortable to return to the countryside to farm.…”
Section: Rural Repulsionmentioning
confidence: 99%
“…The transfer of knowledge and leadership between generations within a family business organization is an exact process that is not easily replicable (Harms, 2014;Zybura et al, 2021a) The previous research found that 30% of family businesses successfully conducted succession between the first and second generations (Wang et al, 2019). However, the success of next-generation succession is more difficult to achieve, thus requiring established planning and strategies (Plana-Farran et al, 2022;Silva et al, 2021;Song et al, 2022). Thus, one of the gaps this research aims to fill is formulating a strategy for the success of a family business succession, considering the previously identified challenges.…”
Section: Introductionmentioning
confidence: 99%